Consumer Acceptance of Dual-Purpose Chickens - A Mixed Methods Approach - Nanke Brum̈mer; Wiebke Petersen; Inken Christoph-Schulz (German Journal of Agricultural Economics (GJAE), 2018)
The killing of day-old male chicks of laying breeds is common practice and is widely discussed within society. There are few alternatives available to replace this practice. One possibility is the use of dual-purpose chicken breeds. The use of these chicken breeds would have implications not only for the entire supply food chain but also for con-sumers. Their meat and eggs have a different ap-pearance, and the resulting products would be more expensive. Furthermore, little is known about consumers' opinions of dual-purpose chickens at present. For this reason, it is essential to explore consumer acceptance of dual-purpose chickens. Mixed methods with a combination of qualitative and quantitative methods proved to be an appro-priate approach to learn more about this matter. The results of six focus groups with an explo-ratory character served as the basis for an online survey with 1,502 respondents in Germany. The data was analysed with the aid of a factor analysis that identified seven factors explaining consumers' attitudes towards dual-purpose chickens. A cluster analysis segmented the respondents into three cluster groups: opponents (37.5%), supporters (23.4%), and indifferents (39.1%). The indifferents represent the largest group of respondents and are therefore an important target group when it comes to potential marketing strategies of products from dual-purpose chickens. The results illustrate the importance of analysing consumer acceptance with regard to emerging issues and before a new product is introduced to the market.
Keywords: 330